2020
DOI: 10.1111/febs.15212
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase 7 (PCSK7) reduces apoA‐V levels

Abstract: The locus of the human proprotein convertase subtilisin-kexin type-7 (PC7) gene (PCSK7) is on chromosome 11q23.3 close to the gene cluster APOA5/APOA4/APOC3/APOA1, a region implicated in the regulation of lipoprotein metabolism. A GWAS reported the association of PCSK7 SNPs with plasma triglyceride (TG), and exome sequencing of African Americans revealed the association of a low-frequency coding variant of PC7 (R504H; SNP rs142953140) with a~30% TG reduction. Another PCSK7 SNP rs508487 is in linkage disequilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
(77 reference statements)
1
23
0
Order By: Relevance
“…In the present work, we studied three polymorphisms (rs508487 T/C, rs236911 C/A, and rs236918 C/G) located on the PCSK7 gene that encodes to the human PCSK7 proprotein. This protein has been implicated in the regulation of apoA-5 and has been associated with a higher triglyceride concentration [3,[6][7][8][9]. In our study, we reported the association of the rs508487 T, rs236911 C, and rs236918 C alleles with the risk of developing ACS.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In the present work, we studied three polymorphisms (rs508487 T/C, rs236911 C/A, and rs236918 C/G) located on the PCSK7 gene that encodes to the human PCSK7 proprotein. This protein has been implicated in the regulation of apoA-5 and has been associated with a higher triglyceride concentration [3,[6][7][8][9]. In our study, we reported the association of the rs508487 T, rs236911 C, and rs236918 C alleles with the risk of developing ACS.…”
Section: Discussionsupporting
confidence: 49%
“…Previous reports have suggested the role of the PCSK7 on plasma lipid levels [6,8,[10][11][12][13]. Therefore, in this study we first explored the potential association of rs508487 T/C, rs236911 C/A, and rs236918 C/G SNPs with total cholesterol, LDL-C, HDL-C, ratio LDL/HDL, and triglyceride plasma concentrations.…”
Section: Association Of Pcsk7 Snps With Plasma Lipids Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coincidentally, this is the locus of PCSK7 that resides close to the gene-cluster APOA5/APOA4/APOC3/APOA1 , a region implicated in the regulation of lipoprotein metabolism (Supplementary Fig. S6 ) 53 .…”
Section: Discussionmentioning
confidence: 99%